ASPEK HUKUM PENILAIAN HARGA YANG WAJAR DALAM PERTUKARAN BARANG - Henry Donald Lombantoruan (Fakultas Hukum Universitas Kristen Indonesia, 2015)
Abstract One of the main principles to ensure economic transactions more efficient and effective is the principle of justice felt by the economic actors. The principle of justice can only be realized if each economic actor mutually agreed upon value (value) of goods and services as well as the currency unit in every economic transaction. In other words, the exchange of (exchange) would not happen if there is no agreement on the value of the underlying economic exchange. In this case, efficient or not an economic system will be determined by how objects are interchangeable assessed. Conditions ‘over-valued’ or ‘under-valued’ of object-exchange will certainly make the transaction does not run efficiently and optimally. Conditions ‘over-valued’ will be very detrimental to consumers and profitable producer or seller. The difference in prices due to ‘over-valued’ is a reflection of the inefficiency of an economy, because consumers should get cheaper products and services. Exchange process in a transaction that took place between economic actors was based on the agreement the fair value of the goods and services both private and state. Fair value (fair value) is basically a reflection of the market value (Market value) of assets. When the fair value opinion generated by the Valuer carried out correctly, of course, will increase improve the quality of financial statements. This is because the value of corporate assets truly reflect the conditions (market value) up to date, so that the company’s assets will not be reported undervalued or overvalued. The problem is, until now we have not had conditions governing special assessment. No new judging partially regulated in the Capital Market Law, Banking and Insurance. In the case there are still many areas that need adjustment of business judgment. The question is, what arrangements benefit assessment? Kata kunci: Aspek Hukum Penilaian Harga Wajar